Сlinical and neuroimmunological correlations in post-stroke epilepsy illustrated by analyzing serum neuron-specific enolase and vascular endothelial growth factor - G. S. Rakhimbaeva; D. S. Sobirova (Эпилепсия и пароксизмальные состояния, 2025)
Background. Due to progress in the treatment of patients who have suffered a stroke, the prevalence of post-stroke epilepsy (PSE) has been increasing. The search for biomarkers that determine the prognosis of ischemic stroke (IS) complications and PSE development along with creating a diagnostic protocol subsequently is useful for advancing tactics of PSE therapy.Objective: to investigate the blood serum levels of neuron-specific enolase (NSE) and vascular endothelial growth factor (VEGF) in PSE patients paralleled by assessing clinical and neuroimmunological correlations.Material and methods. A total of 140 patients aged 28 to 84 years with the first IS was examined. Of these, 70 patients newly developed late epileptic seizures (main group), 70 patients had IS without epileptic seizures (comparison group). The control group consisted of 30 patients without IS or epilepsy. IS severity was assessed according to the National Institutes of Health Stroke Scale (NIHSS), the degree of disability – according to the modified Rankin Scale (mRS), the level of patient’s basic functional activity – according to the Barthel Index (BI). Prediction of post-IS onset of late seizures was performed according to the SeLECT scale (SEverity of stroke, Large artery atherosclerosis, Early seizure, Cortical involvement, Territory of the middle cerebral artery). To assess severity of epilepsy, the K. Lühdorf et al. classification was used. The levels of NSE neurotrophic factor and VEGF angiogenesis factor were measured in blood serum samples from all patients by using enzyme-linked immunosorbent assay (ELISA).Results. A significantly increased NSE and VEGF levels were noted in main group (by 4.72- and 1.59-fold, respectively) and in comparison group (by 4.45- and 1.54-fold, respectively) compared to control group. In addition, NSE and VEGF levels in main group significantly exceeded those in comparison group (by 1.06- and 1.03-fold, respectively). Both biomarkers also tended to increase in patients with moderate and severe PSE. The level of NSE/VEGF correlation characterizing damage to the nervous tissue and angiogenesis as well as degree of severity, disability, rehabilitation potential, patients’ everyday life activity, NSE and VEGF prognostic significance in development and severity level of epilepsy in IS patients with epileptic seizures was determined.Conclusion. NSE and VEGF hyperexpression is important in predicting development or progression (worsening) of epilepsy after IS.